Twelve-month real-world outcomes of sparsentan in a multicentre Spanish IgA nephropathy cohort - Clara García-Carro; Antolina Rodríguez-Moreno; Lucía Cordero; María Vanessa Pérez-Gómez; Helena Marco Rusiñol; Enrique Pasache; Alejandro Morales; Rocío Zamora; Diego Parra; Juan Villa; Elena Guillén-Olmos; Verónica Coll-Brito; et al. (Clinical Kidney Journal, 2026)
Abstract Background Sparsentan has demonstrated significant antiproteinuric effects in randomized trials of IgA nephropathy (IgAN). However, real-world evidence remains scarce and is largely limited to short-term follow-up. Data on the durability of the antiproteinuric response in routine clinical practice are still lacking. Methods This multicenter retrospective study included patients with biopsy-proven IgAN treated with sparsentan in routine clinical practice across Spanish centers. Patients were eligible if they initiated sparsentan outside a clinical trial and had at least 3 months of follow-up. The primary outcome was the proportion of patients achieving a >50% reduction in proteinuria at 3 months (responders). Secondary outcomes included changes in proteinuria and kidney function at 6 and 12 months, as well as safety. Results A total of 41 patients were included. The median age was 42 years, with a median baseline eGFR of 44 mL/min/1.73 m² and 95% receiving concomitant SGLT2 inhibitors. Median baseline proteinuria was 1163 mg/24h. At 3 months, proteinuria decreased to 772 mg/24h (median reduction 44.1%), with 51% of patients achieving a >50% reduction. Among patients with extended follow-up, the antiproteinuric effect was sustained at 6 months (median reduction 46.9%) and persisted at 12 months (median reduction 38.9%), despite increased variability. Notably, kidney function remained stable throughout follow-up, despite a moderately reduced baseline eGFR. No clinically relevant hyperkalemia or severe adverse events were observed. Conclusions In this multicenter real-world Spanish cohort, sparsentan was associated with a sustained reduction in proteinuria in patients with biopsy-proven IgAN, maintained up to 12 months, along with preserved kidney function even in those with moderately reduced baseline eGFR, and a favorable safety profile. These findings support the effectiveness of sparsentan on top of contemporary standard of care and provide early evidence of sustained benefit in routine clinical practice.